2015
DOI: 10.1136/heartjnl-2015-308621.22
|View full text |Cite
|
Sign up to set email alerts
|

22 Role of 12-lead electrocardiography in predicting heart failure in the community

Abstract: PurposeMany patients attending their primary care physician with symptoms suggestive of new onset heart failure, have a 12 lead electrocardiogram (ECG) as part of an initial triage work up. However, the role of ECG in predicting heart failure in the community is not yet defined. We thus examined the ability of ECG to predict heart failure in this patient population.MethodAll 733 patients attending the rapid access clinic for possible heart failure in St Vincent’s University Hospital, Dublin, from the period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to a recent study by Taylor and Hobbs [52], heart failure is associated with abnormal ECG in 89% of the cases. Moreover, James et al [53] showed that heart failure patients have significant prolonged QRS duration, prolonged QT duration, prolonged QTc and more rightward T wave axis. Also, de Luna et al [54] reported long QT interval and visible variations of the shape, amplitude or polarity of the T wave on an alternate-beat basis as ECG changes associated with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study by Taylor and Hobbs [52], heart failure is associated with abnormal ECG in 89% of the cases. Moreover, James et al [53] showed that heart failure patients have significant prolonged QRS duration, prolonged QT duration, prolonged QTc and more rightward T wave axis. Also, de Luna et al [54] reported long QT interval and visible variations of the shape, amplitude or polarity of the T wave on an alternate-beat basis as ECG changes associated with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, it should be noted that patients with a normal NT-ProBNP and abnormal ECG may have underlying atherosclerosis due to diabetes and metabolic syndrome, and this should be excluded particularly if there is no evidence of HF. 30,31 Albuminuria (including both micro-and macroalbuminuria) is another factor that is associated with left ventricular systolic and diastolic dysfunction in T2DM patients and is predictive of CV and HF events. Presence of albuminuria should trigger the suspicion of and confirmation of HF.…”
Section: Early Detection Of Hf In T2dm Patientsmentioning
confidence: 99%
“…23,29,30 In a study on the patient community attending their primary care physicians (PCPs) with symptoms suggestive of new-onset HF, adding BNP to the ECG model was found to increase the robustness in HF prediction (area under the curve [AUC] = 0.88) in the receiver operating characteristic curve analyses as compared to using ECG model alone (AUC = 0.81). 31 The presence of cardiac stress and volume overload leads to the production of NT-proBNP by cardiac ventricles to promote cardioprotection. 32 Evidence from various studies has reflected the role of NT-proBNP in predicting cardiac events, including the risk of HF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations